Towards a more precise diagnosis of hypersensitivity to beta‐lactams — an EAACI position paper - Romano, Antonino; Atanaskovic‐Markovic, Marina; Barbaud, Annick; Bircher, Andreas J.; Brockow, Knut; Caubet, Jean‐Christoph; Celik, Gulfem; Cernadas, Josefina; Chiriac, Anca‐Mirela; Demoly, Pascal; Garvey, Lene H.; Mayorga, Cristobalina; et al. (Allergy (Copenhagen), 2020)
A recent survey of the European Academy of Allergy and Clinical Immunology (EAACI) Drug Allergy Interest Group (DAIG) on how European allergy specialists deal with beta‐lactam (BL) hypersensitivity demonstrated a significant heterogeneity in current practice, suggesting the need to review and update existing EAACI guidelines in order to make the diagnostic procedures as safe and accurate, but also as cost‐effective, as possible. For this purpose, a bibliographic search on large studies regarding BL hypersensitivity diagnosis was performed by an EAACI task force, which reviewed and evaluated the literature data using the GRADE system for quality of evidence and strength of recommendation. The updated guidelines provide a risk stratification in BL hypersensitivity according to index reaction(s), as well as an algorithmic approach, based on cross‐reactivity studies, in patients with a suspicion of BL hypersensitivity and an immediate need for antibiotic therapy, when referral to an allergist is not feasible. Furthermore, the update addresses availability and concentrations of skin test (ST) reagents, ST and drug provocation test (DPT) protocols, and diagnostic algorithms and administration of alternative BL in allergic subjects. Specifically, distinct diagnostic algorithms are suggested depending on risk stratification of the patient into high and low risk based on the morphology and chronology of the reaction, immediate (ie, occurring within 1‐6 hours after the last administered dose) or nonimmediate (ie, occurring more than 1 hour after the initial drug administration), and the reaction severity. Regarding the allergy workup, the main novelty of this document is the fact that in some low‐risk nonimmediate reactions ST are not mandatory, especially in children. For DPT, further studies are necessary to provide data supporting the standardization of protocols, especially of those regarding nonimmediate reactions, for which there is currently no consensus.